The Jellyfish Sign: A New Sonographic Cervical Marker to Predict Maternal Morbidity in Abnormally Invasive Placenta Previa - Bertucci, Emma; Sileo, Filomena Giulia; Grandi, Giovanni; Fenu, Valentina; Cani, Carlotta; Mancini, Luciano; Mataca, Ema; Facchinetti, Fabio (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
Purpose To investigate the value of a new cervical sonographic sign, called the jellyfish sign (JS), for predicting the risk of maternal morbidity in cases of abnormally invasive placenta (AIP) previa totalis.Materials and Methods Retrospective evaluation of transvaginal (TV) and transabdominal (TA) scans performed in all singleton pregnancies with placenta previa totalis. JS, i. e. the absence of the normal linear demarcation between the placenta previa and the cervix, was evaluated by TV scans. The presence/severity of AIP and outcomes of maternal morbidity were related to this sign.Results JS was noted in 8/39 (20.5 %) patients. The two analyzed groups, i. e. with and without JS, were similar. The specificity of JS in AIP diagnosis, histological findings of accreta/increta/percreta, need for caesarean hysterectomy or blood loss > 2000 ml ranges between 92 % and 96.2 %, with the PPV and NPV ranging between 71.4 % and 85.7 % and 61.3 % and 80.6 %, respectively. The JS group had a significant increase in blood loss (ml) (p = 0.003), transfusions (%) (p = 0.016), red blood cells (p = 0.002) and plasma (p = 0.002), admission to an postoperative intensive care unit (ICU) (%) (p = 0.002), hospitalization length (p < 0.001) and the need of cesarean hysterectomy (%) (p < 0.001). JS was independently correlated to cesarean hysterectomy (OR 25.6; 95 % CI 2.0:322.3, p = 0.012) and blood loss > 2000 ml (OR 16.6; 95 % CI 1.5:180.1, p = 0.021) also in a logistic regression model.Conclusion JS is useful in predicting the increase in maternal morbidity: massive transfusion, admission to the ICU and cesarean hysterectomy related to intraoperative bleeding in patients with a previa AIP.
Keywords: placenta accreta; morbidly adherent placenta; ultrasound; cervix; maternal morbidity